Analysis of Character Education in English Textbook for Senior High School Students in Sidrap Regency - Nursamsi Nursamsi; Zulfah Zulfah; Abdul Haris sunubi; Arqam Arqam; Muzdalifah Muzdalifah (Universitas Muhammadiyah Enrekang, 2023)
This research aims to describe the character education values in English Textbooks for the first, second, and third-grade senior high school students in Sidrap Regency. This research is a content analysis using the descriptive-qualitative approach. Data collection used the documentation technique to collect data from the English textbook published by the Ministry of Education and Culture (KEMENDIKBUD). The data analysis procedures used the data analysis model by Ary (2010), including the data organizing stage, data coding stage, and data interpreting stage. The result shows that the English textbook for the first-grade senior high school covers all 18 character education values; the English textbook for the second-grade senior high school encompasses 15 of 18 character values. Meanwhile, the values of independence, appreciation, and nationalism were not found in this textbook. The English textbook for third-grade senior high school contains 15 of 18 character values. Meanwhile, the values of tolerance, democracy, and patriotism were not found in this English textbook.